Pengaruh Gaya Kepemimpinan terhadap Kinerja Auditor dengan Integritas Auditor Sebagai Variabel Moderasi - Fadel Fadel; Arifuddin Arifuddin; Darmawati Darmawati (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This research aims to measure and analyze the effect of leadership style to auditor performance before and after being moderated by integrity auditor. This research design leads to valid, objective, efficient and effective processes and results by using hypothesis testing. The kind of this research uses quantitative method, that used in form of primary data by distribute the questionnaires to respondents. The population in this research were all auditors who work as auditor in Public Accounting Office at Makassar city as many as 8 KAPs, using the saturated sampling method with a total of 50 auditors. Data analysis techniques used include instrument validity test, descriptive statistical analysis, classical assumption test, and hypothesis testing using SPSS 23.0 version. The results of this research show that leadership style has a positive and significant effect to auditor performance as well as the results that obtained after being moderated by integrity auditor. The results of this research can be used as a basis for determining policies by Public Accounting Office to assess the performance of their auditors